2013
DOI: 10.1177/2150131913475817
|View full text |Cite
|
Sign up to set email alerts
|

Subutilization of COPD Guidelines in Primary Care

Abstract: Despite the existence and availability of evidence-based guidelines, only a minority of primary health care COPD patients in Mexico are receiving state-of-the-art treatment at the primary care level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 14 publications
0
6
0
2
Order By: Relevance
“…The results of the PLATINO survey suggest that primary care physicians may require additional training to better manage COPD patients in Latin America [84,85]. Integrated programs, such as the Practical Approach to Lung Disease [86][87][88][89], may help manage COPD as well as other respiratory conditions such as acute respiratory infections, pneumonia, tuberculosis and others depending on the country or region.…”
Section: A Primary Care Approach To Copd In Latin Americamentioning
confidence: 99%
“…The results of the PLATINO survey suggest that primary care physicians may require additional training to better manage COPD patients in Latin America [84,85]. Integrated programs, such as the Practical Approach to Lung Disease [86][87][88][89], may help manage COPD as well as other respiratory conditions such as acute respiratory infections, pneumonia, tuberculosis and others depending on the country or region.…”
Section: A Primary Care Approach To Copd In Latin Americamentioning
confidence: 99%
“…The evidence-based guidelines available to aid physicians in the management and treatment of patients are frequently not fully implemented in clinical practice, as demonstrated across many regions worldwide. 4 11 Reasons for this include a lack of familiarity with guidelines and a lack of confidence in implementation and access/time constraints, 9 11 but have also been shown to be associated with physician perceptions and beliefs about COPD management. Yawn et al 10 reported that among 278 primary care physicians (PCPs) and practice nurses/assistants, only 15% thought COPD treatments were very or somewhat useful and 3% thought pulmonary rehabilitation was useful or very useful, despite its availability to 32% of those sampled.…”
Section: Introductionmentioning
confidence: 99%
“… 4 7 A large web-based survey in 2011 of primary care physicians (PCPs) across the regions of Asia Pacific, Africa, Eastern Europe, and Latin America showed limited knowledge of COPD guidelines, including underutilization of spirometry for diagnosis of COPD and a general lack of awareness about the significance of exacerbations as an important factor in the management of COPD. 8 Country-specific surveys largely conducted in primary care in Western Europe, 5 , 6 , 9 11 Japan, 12 Mexico, 13 and the USA 14 16 have also shown that despite knowledge of guidelines, there is a lack of adherence to guideline recommendations for the treatment of COPD. In the USA, the main barriers to guideline implementation have been reported as low familiarity, low ability or confidence in interpreting recommendations, time constraints, and low outcome expectancy among physicians.…”
Section: Introductionmentioning
confidence: 99%